Classification and expression analysis of cucumber (Cucumis sativus L.) callose synthase (CalS) family genes and localization of CsCalS4, a protein involved in pollen development. Issue 1 (1st January 2021) - Wang, Hongyun; Cao, Shoujun; Li, Tao; Zhang, Lili; Yao, Jiangang; Xia, Xiubo; Zhang, Ruiqing
Abstract: Callose plays an important role in plant development and response to multiple biotic and abiotic stresses. Callose synthase (CalS; EC 2.4.1.34), the main enzyme in callose synthesis, has been studied in a number of crops but not in cucumber ( Cucumis sativus L.). In this study, 10 genes encoding putative callose synthase were identified and classified into four clades. Expression levels of the 10 CsCalS genes, which varied considerably, were detected in most analyzed organs. Transcription of CsCalS1 and CsCalS8 was obviously induced by downy or powdery mildews, which are pathogenic fungi of cucumber. CsCalS4, which was highly expressed in male flowers, was chosen for further study. Expression analysis revealed that CsCalS4 was mainly expressed in anther, and highly expressed at the stage of anther meiosis (St10), and uninuclear pollen appearance stage (St11). Histochemical and subcellular localization analyses indicated that CsCalS4 was mainly present in pollen grains and primarily localized in the plasma membrane. The results of this study provided a basic understanding of CsCalS genes and suggest the involvement of CsCalS4 in pollen development.